PENGARUH KREATIVITAS DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP AL-IJTIHAD KOTA TANGERANG - Zubaidi, Zubaidi (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
This study aims to describe the relationship between creativity and learning style on student achievement in Islamic Religious Education lessons at SMP Al-Ijtihad Tangerang City. The approach used in this research is a quantitative approach with the type of correlation research. The population in this study were students of SMP Al-Ijtihad Tangerang City with a population of 270 people and a sample of 100 people. The data collection technique was carried out with a questionnaire to obtain data on creativity and learning styles, and PAI learning achievement. The analysis used in this research is multiple correlation analysis. The results of this study indicate that (1) There is a positive and significant relationship between creativity and learning achievement of Islamic Religious Education, namely ryx1 = 0.988 with very strong criteria. And creativity has a role of 97.61% on student achievement in Islamic Religious Education lessons; (2) There is a positive and significant relationship between learning styles and student achievement in Islamic Religious Education lessons, namely ryx2 = 0.985 with very strong criteria. And learning styles have a role of 97.02% of student achievement in Islamic Religious Education lessons; (3) There is a positive and significant relationship between creativity and learning style on student achievement in Islamic Religious Education lessons, namely ryx1x2 = 0.989 with very strong criteria. And creativity and learning styles simultaneously (together) have a role of 97.81% of student achievement in Islamic Religious Education lessons.